Grapevine Red Blotch-Associated Virus, an Emerging Threat to the Grapevine Industry - Sudarshana, Mysore R; Perry, Keith L; Fuchs, Marc F (Phytopathology, 2015)
Grapevine red blotch-associated virus (GRBaV) is a newly identified virus of grapevines and a putative member of a new genus within the family Geminiviridae. This virus is associated with red blotch disease that was first reported in California in 2008. It affects the profitability of vineyards by substantially reducing fruit quality and ripening. In red-berried grapevine cultivars, foliar disease symptoms consist of red blotches early in the season that can expand and coalesce across most of the leaf blade later in the season. In white-berried grapevine cultivars, foliar disease symptoms are less conspicuous and generally involve irregular chlorotic areas that may become necrotic late in the season. Determining the GRBaV genome sequence yielded critical information for the design of primers for polymerase chain reaction-based diagnostics. To date, GRBaV has been reported in the major grape-growing areas in North America and two distinct phylogenetic clades have been described. Spread of GRBaV is suspected in certain vineyards but a vector of epidemiological significance has yet to be identified. Future research will need to focus on virus spread, the production of clean planting stocks, and the development of management options that are effective, economical, and environmentally friendly.